Enhancing biofilm formation in biofilters for benzene, toluene, ethylbenzene, and xylene removal by modifying the packing material surface. (January 2020) - Sun, Zhuqiu; Ding, Cheng; Xi, Jinying; Lu, Lichao; Yang, Bairen
Graphical abstract: Highlights: Surface of polyurethane(PU) sponges were modified. Higher surface roughness and positive charge were obtained on PU sponges surface. Utilization of the modified PU sponges could enhance BTEX removal in biofilter. Effects of modified PU sponge for biofilm formation in biofilter were investigated. Abstract: Polyurethane (PU) sponges are popular packing material in biofilters and their smooth and hydrophobic surface often leads to an uneven distribution and detachment of biofilms. In this work, the surface of PU sponge was modified to obtain higher roughness and positive charge. The performances of two biofilters (BF1 with pristine sponge and BF2 with modified sponge) for benzene, toluene, ethylbenzene, and xylene (BTEX) removal were investigated. Total Volatile Organic Compound (TVOC) removal efficiency and CO2 increment were 61% and 804 ppm for BF2 respectively after start-up, compared with 51% and 538 ppm for BF1. Analysis on biofilms showed that the modification of PU sponge significantly improved the microbial growth, viability and adhesive strength in biofilms, reduced extracellular polymeric substance (EPS) and changed the microbial community. These results demonstrate that modified sponge can enhance biofilm formation and BTEX removal in biofilters and may applied in large-scale applications.